2013
DOI: 10.1186/1471-2393-13-93
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, determinants and perinatal outcomes of near miss maternal morbidity in Ile-Ife Nigeria: a prospective case control study

Abstract: BackgroundMaternal mortality ratio in Nigeria is one of the highest in the world. Near misses occur in larger numbers than maternal deaths hence they allow for a more comprehensive analysis of risk factors and determinants as well as outcomes of life-threatening complications in pregnancy. The study determined the incidence, characteristics, determinants and perinatal outcomes of near misses in a tertiary hospital in South-west Nigeria.MethodsA prospective case control study was conducted at the maternity unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
87
6
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 24 publications
28
87
6
13
Order By: Relevance
“…Together, they were the reasons for admission for 64% of the women. This finding is consistent with earlier studies (22)(23)(24)(25). The high incidence of hypertensive disorders of pregnancy in the studied women may be due to poor dietary habits, lack of exercise and more stressful conditions in pregnancy.…”
Section: Boxsupporting
confidence: 82%
“…Together, they were the reasons for admission for 64% of the women. This finding is consistent with earlier studies (22)(23)(24)(25). The high incidence of hypertensive disorders of pregnancy in the studied women may be due to poor dietary habits, lack of exercise and more stressful conditions in pregnancy.…”
Section: Boxsupporting
confidence: 82%
“…In some of the African countries like Gambia, Nigeria and Sudan a higher risk of still birth was also observed among women of near miss when compared to women without near miss [17][18][19][20]. Hence, this is indicative of the link between still birth and maternal near miss.…”
mentioning
confidence: 81%
“…The studies that were included in this Meta-analysis used different identification criteria to define the exposure(maternal near miss).One of the studies used the WHO criteria [29], some used disease based [17,28],the other disease plus management based [19] and the rest used pragmatic definitions [15]. Using different identification criteria to identify maternal near miss cases might have its own impact for the observed heterogeneity of the studies.…”
Section: Limitation Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated individual medical comorbidities, such as pre-existing asthma, hypertension, malignancy, chronic ischaemic and congenital heart disease, chronic renal disease, systemic lupus erythematosus, hypercoagulability states, human immunodeficiency virus and diabetes mellitus, to be associated with both severe maternal morbidity and mortality, 25,153,[162][163][164][165][166][167][168] but the extent of the population risk attributable to medical comorbidities as a whole in the UK has not previously been quantified. Uptake of antenatal care was found to be poorer among women with medical comorbidities in our study population, which could increase the adverse effects associated with these conditions.…”
Section: Conclusion and Implications For Policy And Practicementioning
confidence: 99%